Clinical Phenotypes of Autosomal Recessive Ataxias - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
An overview of the most common autosomal recessive cerebellar ataxias is presented by researchers at the UCLA Ataxia Center, Los Angeles.